Relationship Between Body Mass Index and Chronic Periodontitis - Aryal, Shreeya; Pradhan, Ameena; Shrestha, Shilu; Shrestha, Surendra Man (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Obesity is regarded as unnecessary body fat in ratio to lean body mass. Besides being an established risk factor for cardiovascular and other systemic diseases, obesity has been suggested to be a potential threat for periodontitis as well.Objective: The objective of the study was to learn relationship between body mass index (BMI) and periodontal disease.Methods: This analytical cross-sectional study was conducted at People’s Dental College from February 16 to April 15, 2021 after ethical approval. Seventy-two participants were selected conveniently who, on the basis of calculation of weight and height were allocated into two groups: Group A: participants with normal BMI, Group B: Obese/ overweight individuals. Plaque index, gingival index, periodontal pocket, and clinical attachment loss were recorded in both the groups to assess the periodontal disease status. On basis of findings, the two groups were statistically compared.Results: The result showed clinical attachment loss was significantly higher (P